ANALYSISOF ENGLISH WORD FORMATIONIN "HIGH END TEEN" MAGAZINE IN JUNE 2008 EDITION - Geos Triany, - (2011)
The paper entitled "Analysis of English Word Formation in "HighEnd Teen" Magazine in June 2008 edition" is aimed to reveals the English word formation processes and investigates the change of basic meaning from the derived words occurred in seven articles of the magazine. The analysis mainly uses a descriptive qualitative method based on O'Grady and Guzman (1996), Yule (1996), and Nick Cipollone, Steven Hartman Keiser, and Shravan Vasishth theories of word formation processes. In addition, Oxford Advanced Learner's Dictionary 7th edition by Wehmeier, S, Ed. is also used to support the analysis. Findings show that young people are very innovative and creative in the language used in the magazine. It is supported by some English word formation processes found in the magazine i.e. acronym, blending, and clipping. It also shows that young people try to make simple language that could be mentioned easily and shortly. Interestingly, clipping process found in this teenager magazine supports the statement of O'Grady and Guzman that clipping is famous among students. In addition, the findings show that the clipping of prom, phys ed, eco, phone, and gym are famous among students. Besides acronym, blending, and clipping, other English word formation processes that are also found in this study are compounding and derivation-especially prefix and suffix. Suffix is the most frequent word formation used in the magazine, followed by compound, prefix, clipping, acronym, and blending which is the least frequent word formation used in the magazine.